2004
DOI: 10.1007/s00134-004-2504-1
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed medical therapy and point-of-care testing improve outcomes after congenital heart surgery

Abstract: The combination of goal-directed therapy and point-of-care testing was associated with a marked decrease in mortality for patients undergoing congenital heart surgery. Improvement was greatest in the highest risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…It may be used to prognosticate outcome or as an end point of resuscitation in critical illness [3][4][5][6][7] . In children recovering from congenital heart surgery, the degree of hyperlactatemia is directly related to mortality [5] .…”
Section: Discussionmentioning
confidence: 99%
“…It may be used to prognosticate outcome or as an end point of resuscitation in critical illness [3][4][5][6][7] . In children recovering from congenital heart surgery, the degree of hyperlactatemia is directly related to mortality [5] .…”
Section: Discussionmentioning
confidence: 99%
“…A study compared a prospective cohort of 710 postoperative cardiac patients with an historical cohort of 1656, following the introduction of a treatment protocol in which medial therapy was escalated if blood lactate levels were >5 mmol/L 40. A mortality difference was only identified in children under 1 year of age, most significantly for neonates (3.4% vs 12%, p=0.001).…”
Section: Indications and Limitationsmentioning
confidence: 99%
“…4 However, the role of lactate as a marker in goal-directed therapy is less clear. 2,4 However, lactate levels can be helpful when examined as a trend, and rising lactate levels should prompt further evaluation of the patient. 17 Similarly, lactate levels can also be elevated by seizures, shivering, large volume resuscitation of lactated ringers, liver dysfunction, acute lung injury, and exogenous catecholamine infusions.…”
Section: Lactatementioning
confidence: 99%
“…2 The use of goal-directed therapy is not unique to adult critical care. In an article published that year in the New England Journal of Medicine, Rivers et al 1 showed a significant reduction in the mortality of adult septic shock patients with early goal-directed therapy.…”
mentioning
confidence: 99%